Lower bile acids as an independent risk factor for renal outcomes in patients with type 2 diabetes mellitus and biopsy-proven diabetic kidney disease - Xiao, Xiang; Zhang, Junlin; Ji, Shuming; Qin, Chunmei; Wu, Yucheng; Zou, Yutong; Yang, Jia; Zhao, Yuancheng; Yang, Qin; Liu, Fang (Frontiers in Endocrinology, 2022)
Aims: Abnormalities of glucolipid metabolism are critical mechanisms involved in the progression of diabetic kidney disease (DKD). Bile acids have an essential role in regulating glucolipid metabolism. This study investigated the clinicopathological characteristics of DKD patients with different bile acid levels and explored the relationship between bile acids and renal outcomes of DKD patients. Methods: We retrospectively reviewed and evaluated the histopathological features and clinical features of our cohort of 184 patients with type 2 diabetes mellitus and biopsy-proven DKD. Patients were divided into the lower bile acids group (≤2.8 mmol/L) and higher bile acids group (>2.8 mmol/L) based on the cutoff value of bile acids obtained using the time-dependent receiver-operating characteristic curve. Renal outcomes were defined as end-stage renal disease (ESRD). The influence of bile acids on renal outcomes and correlations between bile acids and clinicopathological indicators were evaluated. Results: Bile acids were positively correlated with age (r = 0.152; P = 0.040) and serum albumin (r = 0.148; P = 0.045) and negatively correlated with total cholesterol (r = -0.151; P = 0.041) and glomerular class (r = -0.164; P =0.027). During follow-up, 64 of 184 patients (34.78%) experienced progression to ESRD. Lower levels of proteinuria, serum albumin, and bile acids were independently associated with an increased risk of ESRD (hazard ratio, R=5.319; 95% confidence interval, 1.208–23.425). Conclusions: Bile acids are an independent risk factor for adverse renal outcomes of DKD patients. The serum level of bile acids should be maintained at more than 2.8 mmol/L in DKD patients. Bile acid analogs or their downstream signaling pathway agonists may offer a promising strategy for treating DKD.